Laser nanodissection for intracellular actin stress fibers and analysis of the severed fiber retraction and regeneration behavior - Chiho KAMBE; Kazuaki NAGAYAMA (Nihon Kikai Gakkai ronbunshu)
The intracellular actin cytoskeleton binds to non-muscle myosin II to form stress fibers (SFs) with a diameter of several hundred nanometers, which generate intracellular tension and control cell shape and movement. SFs generate a contractile force and transmit it to focal adhesions, which is essential for regulation of cell adhesion to extracellular matrix and cellular sensing of extracellular mechanical environments. Although several studies have been reported on the mechanical and contractile properties of SFs, it has not been clear how completely severed SFs are repaired and regenerated. In this study, SFs located at the periphery of living myoblasts (C2C12) were severed using a pulsed laser and their contraction and repair process were analyzed by fluorescence observation. SFs immediately contracted after their severing. The contraction process of SFs was accurately fitted using the first order lag model, indicating viscoelastic behavior. We found that SFs have a potential to repair their structures: in approximately 80% of the cells, the structure of severed SFs was gradually repaired over several minutes with contraction behavior (Repaired group), but not in some cells (Unrepaired group). The contraction rate α and contraction time constant τ of the SFs in the unrepaired group tended to be larger than those of the repaired group. These results suggest that the repair process of the severed SFs is possibly affected by the intrinsic mechanical tension of the SFs and viscous resistance from the intracellular components around the SFs which is generated by the sliding motion caused by the fiber contraction.